Alberto Jiménez, Juan Valera y la generación de 1868. The Dolphin Book Co., Oxford, 1956; 117 pp. - Ontañón de Lope, Paciencia (El Colegio de México, 1959)
Se reseñó el libro: Juan Valera y la generación de 1868.